Wetting Properties and Foliar Water Uptake of Tillandsia L. (September 2019) - Zambrano, Anna Rose C.; Linis, Virgilio C.; Nepacina, Maria Rejane J.; Silvestre, Mark Louie T.; Foronda, Juanito Raphael F.; Janairo, Jose Isagani B.
Abstract: Quantitative dimensional analyses of the wetting property of selected Tillandsia L. were conducted. The wettability on the leaf surfaces of three Tillandsia species and one hybrid cultivar has significant variations ( p < .05). This variation is influenced by their absorptive foliar trichomes. The structure, arrangement and density of their foliar trichomes on the leaf surfaces and the degree of corrugated trichome wings with variations on micro−/nano-protrusion allow the liquids to increase its spreading and/or liquid repellency. Among the Tillandsia species, T. schiedeana Steudel has the densest trichomes. The average trichome densities are as follows: T. schiedeana (61.20 mm 2 ± 3.36) has the highest and T . Houston ( T. stricta Sol. ex Sims T. recurvifolia Hook) hybrid (45.24 mm 2 ± 5.93) has the lowest trichome density on the adaxial leaf surface; while T. schiedeana (63.55 mm 2 ± 10.46) has the highest and T. xerographica Rohweder (40.66 mm 2 ± 17.72) has the lowest trichome density found on the abaxial leaf surface ( p < .0001). All examined Tillandsia exhibited foliar water uptake. One of them, T. schiedeana had significantly greater increase in leaf water content up to 115.9% followed by T . Houston (57.37%) > T. xerographica (36.63%) > T. caput-medusae E. Morren (35.91%). Based on the results of adhesion and surface free energy of the leaf surfaces, the desirable wetting properties of all four Tillandsia plants used in this study were determined. Among the four, T. schiedeana and T. caput medusae exhibited interesting liquid adhesion on the adaxial leaf surface which makes the two plants hydrophilic on this particular leaf surface. On the other hand, the highest water drop adherence to the leaf surface is observed in T. schiedeana which is necessary for its high foliar water uptake. In this study, it was proven that structure, arrangement and density of foliar trichomes found in Tillandsia affect the spreading of liquid and leaf surface wettability on their leaf surfaces which in turn improve the foliar water uptake of these plants. Highlights: For the first time, we're able to provide quantitative dimensions on the wettability of the water absorbing leaves of the examined Tillandsia species. The structure, arrangement and density of the foliar trichomes on the leaf surfaces and the degree of corrugated trichome wings with variations on micro-protrusions allow the liquids to increase its spreading and/or repellancy of the examined species. There are variations on the wettability of the leaf surfaces of the examined Tillandsia species. The adaxial leaf surface tends to have higher adhesion and higher liquid spread compared to abaxial leaf surfaces. This is due to the variations of their trichome density and micro-structure of the trichomes. The unique foliar trichome wings that influence interesting wetting and liquid adherence exhibited by the leaf surfaces of the four examined Tillandsia species will attract future researches for innovations of bioinspired materials